2016
DOI: 10.1016/j.jhin.2016.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve patient hand hygiene: a systematic review

Abstract: Nosocomial pathogens may be acquired by patients via their own unclean hands, but there has been relatively little emphasis on patient hand hygiene as a tool for preventing healthcare-associated infections (HCAIs). The aim of this systematic review was to determine the efficacy of patient hand hygiene interventions in reducing HCAIs and improving patient hand hygiene rates compared to usual care. Electronic databases and grey literature were searched to August 2014. Experimental and quasi-experimental studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 17 publications
(15 reference statements)
0
26
0
Order By: Relevance
“…This study emphasises that there is a persisting different attitudinal perception among patients and nursing staff. Based on the findings of Srigley et al's systematic review, 17 there is a need for study designs that are more rigorous. This study, while only a descriptive study, builds on this body of work as there is a scarcity of literature on hand hygiene studies with patients at the core.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This study emphasises that there is a persisting different attitudinal perception among patients and nursing staff. Based on the findings of Srigley et al's systematic review, 17 there is a need for study designs that are more rigorous. This study, while only a descriptive study, builds on this body of work as there is a scarcity of literature on hand hygiene studies with patients at the core.…”
Section: Resultsmentioning
confidence: 99%
“…A recent systematic review conducted by Srigley et al 17 reported successful hand hygiene interventions in patients and health care workers. Their findings emphasise a lack of rigor in the study design of the 10 studies that were included in their review.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Building on patient hand hygiene as a concept for infection control, future studies should focus on well-designed trials with patient hand hygiene interventions, measures of pathogen colonization and infection, and what role patient hands may have in self-inoculation.…”
Section: Discussionmentioning
confidence: 99%